CONTENT AND PROGNOSTIC VALUE OF SOME CYTOKINES IN BLOOD SERUM AND FOLLICULAR FLUID IN WOMEN WITH POLYCYSTIC OVARY SYNDROME PARTICIPATING IN THE IVF PROGRAM - Виктория Васильевна Лихачева; Раиса Михайловна Зорина; Людмила Григорьевна Баженова; Аркадий Геннадьевич Маркдорф; Светлана Викторовна Архипова; Сергей Николаевич Филимонов (Медицина в Кузбассе, 2017)
Research objective. Study of the content as well as the effect on IVF program outcomes of certain cytokines (tumor necrosis factor-alfa (TNF-α), interleukins 6 and 8 (IL-6 and IL-8), as well as interferon gamma (IFN-γ) in blood serum and follicular fluid in infertile female with polycystic ovarian syndrome (PCOS) and tubal factor of infertility.